Dana Amil Baznas Makassar Psak 109 Vs Praktik - Mochammad Fadhil Abdullah; Muhammad Wahyuddin Abdullah; Saiful Muchlis; Rahmawati Muin; Ayu Ruqayyah Yunus (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
Amil has a maximum right of 12.5% of zakat funds while for infaq / alms funds and other religious social funds, a maximum of 20% of amil rights are used for amil operational purposes. Amil is required to make disclosures related to transactions, and distribution policies including funds for amyl itself as well as the percentage of distribution, and the reason for the policy used. In the financial statements according to PSAK 109, amil funds are presented in the statement of financial position and statement of changes in funds and disclosed in notes to the financial statements. This study aims to determine the compatibility between the practice of presenting and disclosing amil funds/rights in the financial statements of BAZNAS Makassar City with PSAK Standard 109 concerning Accounting for Zakat, Infaq, and Alms Management. This research was carried out with a descriptive qualitative approach with literature studies. This qualitative research tries to provide an overview of theory with practice in the field after comparing the two. The type of data used is secondary data. The data used is secondary data that has been provided by BAZNAS in the form of audited financial statements for 2022 and 2021. The results of this study show that the components of the Audited financial statements of BAZNAS Makassar City 2022-2021 in format have followed the PSAK 109 standard consisting of a Balance Sheet, Report of Changes in Funds, Report of Changes in Managed Assets, Cash Flow Statement and Notes to Financial Statements. However, the presentation and disclosure are not following PSAK 109 and generally accepted financial accounting standards.